Feeding Associations With Speech And Language Using Tdsc And Lest Charts (Journal of Pharmaceutical Negative Results, 2023)
Feeding habits of children and its association with language development depends on the age at texture transitions, feeding phase (breastfeeding, weaning to solids or full solids), characteristics of the meal (duration, environment, and shared meals with adults),feeding practices, use of feeding equipment and bottle, digital or pacifier suction. The World Health Organization (WHO) recommends exclusive breastfeeding during the first six months of life and from this age, onwards, other foods and liquids are gradually introduced into the child's diet, and this transition should be carefully followed up by a professional.(1)Early weaning or unexercised sucking may culminate in the establishment of deleterious oral habits such as pacifier use, digital suction and oral breathing. These frequently demonstrate a relation to occlusal disarrangement, besides being able to justify changes in swallowing, breathing and speech functions.(2)